Փոքրիկ երկրի ձեռագրական մեծ գանձերը - Հնձացեան, Գեւորգ; Գալստեան, Արշալոյս (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Создание и сохранение рукописей в Средние века было важной задачей для большинства цивилизованных и цивилизующихся народов. Эти древние рукописные памятники сегодня представляют собой неоценимое духовное и культурное наследие, позволяющее судить об отношении народов к науке, образованию и просвещению. На фоне статистических данных о количестве средневековых рукописей, сохранившихся в Европе и Востоке, рукописное наследие Армении — около 30 000 армянских рукописей, дошедших до наших дней — представляется исключительным достижением, особенно с учётом драматической исторической судьбы армянского народа. В этом контексте монография кандидата исторических наук Арпеник Газаросян «Писцовые центры страны Гегама и рукописное наследие», изданная по решению Научного совета Матенадарана имени Месропа Маштоца, представляет собой уникальное исследование, посвящённое истории рукописной культуры Севанского бассейна (исторической страны Гегама). Автор изучает 67 сохранившихся рукописей из региона, подробно анализируя как их содержание, так и обстоятельства их создания, включая биографии писцов и историю писцовых центров. Газаросян использует широкий круг источников — от эпиграфики и памятных записей до литературных преданий и новейших научных публикаций, что делает исследование глубоко оригинальным и научно значимым. Монография состоит из 300 страниц, включает как историко-источниковедческий, так и рукописоведческий анализ, и впервые предлагает систематизированное картографирование рукописных центров страны Гегама. Исследование охватывает как раннесредневековый, так и позднесредневековый периоды, уделяя особое внимание таким центрам, как Севанский монастырь, Макиняцкий обитель, деревни Котагех, Хороваканк, Даранакс и другие. Работа Газаросян может служить моделью для аналогичных исследований в других регионах Армении. Значение этой монографии заключается не только в научной новизне, но и в её прикладной ценности: книга может использоваться в образовательных целях и как основа для программ по переоценке культурного наследия Севанского региона. The creation and preservation of manuscripts was a crucial cultural endeavor for nearly all civilized and civilizing nations during the Middle Ages. Today, this handwritten legacy is considered an invaluable treasure, both spiritually and intellectually. An overview of manuscript holdings in various European countries—ranging from over 80000 in the Vatican Library to several hundred in Baltic states—illustrates the historical efforts of each nation in preserving its intellectual heritage. Despite facing severe hardships throughout its history, Armenia has succeeded in preserving approximately 30 000 medieval Armenian manuscripts, a testament to the resilience and cultural devotion of its people. In this context, the monograph “The Scriptoria and Manuscript Heritage of the Land of Gegham” by Arpenik Ghazarosyan, candidate of historical sciences and longtime lecturer at the Vazgenian Seminary of Sevan and the Gevorkian Theological Seminary, emerges as a fundamental scholarly work. Published with the approval of the Scientific Council of the Matenadaran (Mesrop Mashtots Institute of Ancient Manuscripts), the study focuses on the history of manuscript production in the Gegham region (present-day Sevan basin), revealing that only 67 manuscripts from this area have survived. With thorough attention to detail and an interdisciplinary methodology, the author not only analyzes the content, script, and provenance of these manuscripts but also reconstructs the historical background of the scriptoria through epigraphic, codicological, and bibliographical sources. The monograph is structured into four comprehensive chapters and presents detailed case studies on specific scriptoria, including Sevan, Makenis, Noratus, Hayravank, and others. It also offers a complete mapping of Gegham’s scriptoria, identification of previously unknown manuscripts, and reconstruction of scriptorium activities through colophons and historical data. Ghazaryan’s methodological rigor— particularly the integration of manuscript colophons with epigraphic and historiographic evidence—sets a new standard in Armenian manuscript studies. The work not only contributes to medieval Armenian cultural history but also serves as a model for future regional manuscript research and can be utilized in academic curricula and heritage preservation projects.
Keywords: Գրախօսութիւն